2017
DOI: 10.24127/gdn.v7i1.797
|View full text |Cite
|
Sign up to set email alerts
|

Contribution Locus of Control and Self Esteem to Student Academic Procrastination (Study at Department of Islamic Guidance And Counseling, IAIN IB Padang)

Abstract: This study aims to: (1) describe the locus of control, self-esteem and student academic procrastination (2) express the contribution of locus of control and self-esteem to student academic procrastination. This research is conducted by the expost-facto method with questionnaire instrument which has been measured its validity and reliability. The population in this study were BKI FTK IAIN IB Padang students entering 2014, 2013 and 2012 totaling 355 people, the samples used were Stratified Proportional Random Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…I am continually saying I'll do it tomorrow". Items 3,4,6,8,11,13,14,15,18,and 20 were reverse scored items, whereby higher scores for these items indicated less academic procrastination. The reverse scored items were such as "3.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…I am continually saying I'll do it tomorrow". Items 3,4,6,8,11,13,14,15,18,and 20 were reverse scored items, whereby higher scores for these items indicated less academic procrastination. The reverse scored items were such as "3.…”
Section: Methodsmentioning
confidence: 99%
“…In everlasting fight against academic procrastination: The roles of classroom engagement … (Yen Ling Hui) 649 problematic behaviours that contributes to their academic challenges [29]. Similarly, an ex-post facto study on academic procrastination was conducted with a sample size of 107 students from an Islamic educational institution [6]. The study found that students with high internal locus of control believe that their effort determines the outcome of their success or failures, and their belief enables them to feel more confident about themselves, which explains their higher levels of effort and ability to accomplish tasks on time.…”
Section: Issn: 2252-8822 mentioning
confidence: 99%
See 3 more Smart Citations